Possibilities and restrictions of heavy-mineral analysis for the reconstruction of sedimentary environments and source areas - Derkachev, A.N.; Nikolaeva, N.A. (Geologos, 2013)
The possible reconstruction of ancient sedimentary environments on the basis of heavy-minerals assemblages is presented by means of discriminant lithogeodynamic diagrams that compare modern and ancient sedimentary environments. This is exemplified by Mesozoic-Cenozoic deposits recovered from ODP cores obtained from the Philippine and Japan Seas, the Japan Trench and the North Atlantic, as well as by deposits from folded areas onshore. On the basis of the comparative analysis, it can be deduced that the main tendencies in mineral assemblages of modern deposits that depend on the structural-tectonic conditions, are fairly well preserved in Cenozoic deposits (including the deposits recovered by ODP drilling). On the other hand, the environmental reconstruction of folded and faulted pre-Cenozoic continental areas on the basis of their heavy-mineral assemblages, by comparing them with supposed modern analogs, is not always possible with much certainty. The main reasons may be either a considerable change in the composition of the initial (primary) mineral assemblages as a result of intralayer solution or the absence, at the time of deposition, of geodynamic environments that closely resembled modern ones.